Japanese for Travelers Useful Phrases, Travel Tips, Etiquette - Scott Rutherford (Tuttle Shokai Inc, 2009)
Packed with expressions and information for every travel situation, Japanese for Travelers Phrasebook & Dictionary helps you to get around and communicate more effectively during your time in Japan. This book includes hundreds of tips and phrases for the following situations: Meeting people Asking directions Shopping and asking about prices Ordering food and drinks Getting connected to the Internet Taking a subway, bus or taxi Asking for help Daily conversations Helpful illustrations demystify Japan's complicated rail system and provide handy information on ferry travel as well. The text offers tips on where to look for a cheap, comfortable night's sleep (you'd be surprised), to whom not to stand behind when in line at customs, as well as essential things to purchase for your Japan trip before you leave your home country and how to say you do not eat fugu (poisonous pufferfish!).